Effects of different vaccination regimes on the immunodiagnosis of tuberculosis in goats and evaluation of defined antigens - Patricia Cuenca-Lara; Patricia Cuenca-Lara; Miriam Blay-Benach; Miriam Blay-Benach; Zoraida Cervera; Zoraida Cervera; Cristian Melgarejo; Cristian Melgarejo; Julia Moraleda; Julia Moraleda; Iker A. Sevilla; Joseba M. Garrido; et al. (Frontiers in Veterinary Science)
Tuberculosis (TB) in goats is a chronic infectious disease caused by Mycobacterium tuberculosis complex (MTBC) organisms that pose a great health and economic challenge for the caprine industry in some European and developing countries. It is also a zoonotic disease posing a risk for public health. The control programs of the disease are based on a test-and-slaughter strategy, and vaccination is not feasible with available vaccines due to its interferences with the current TB immunodiagnosis. There is still a need for the development of an effective TB vaccine and, concurrently, diagnostic methods that allow differentiation between infected and vaccinated animals (DIVA approach). In this study, we investigated the interferences caused by the tuberculin (PPD)-based TB diagnostic tests in goats immunized by different mucosal and parenteral vaccination strategies: three single-dose strategies based on intranasal administration of BCG and two heat-inactivated M. bovis (HIMB) vaccines, and two prime-boost strategies based on parenteral BCG or HIMB priming and intranasal HIMB boosting. In addition, the defined antigens ESAT-6, CPF10, and EspC were evaluated as alternative diagnostic reagents to PPDs. At week 14 after prime vaccination of the animals, skin tests, IFN-γ release assay, and antibody detection assays were performed. The two prime-boosted and the single-dose intranasal BCG groups displayed greater cell-mediated immune responses to PPDs than the two single-dose intranasal HIMB vaccines. However, the use of reagents based on the defined antigens eliminated or reduced the vaccine-induced diagnostic interferences in all groups. Based on these results, the use of defined antigens in the current immunodiagnostic tests appears to be suitable in a future goat TB vaccination scenario.